ANESTHETIC EFFECT OF CLOVE (Eugenia aromaticum) SEED EXTRACT ON Clarias gariepinus (BURCHELL, 1822) FINGERLINGS UNDER SEMI ARID CONDITION - Diyaware, Mohammed Yakubu; Akinwande, Akinlolu Ademuyiwa; Aliyu, Mohammed (Journal of Agricultural Sciences (Belgrade), 2017)
The anesthetic effects of Clove (Eugenia aromaticum) seed extract on Clarias gariepinus fingerlings were investigated under semi-arid condition. Various concentrations of the clove seed extract at 25.0, 50.0, 75.0, 100.0, 125.0 and 150.0mg/per liter of water were used for the experiment. Each concentration was tested on a group of 10 Clarias gariepinus fingerlings (24.13 - 25.30g weight and 5.97 - 7.00 cm length) in glass aquariums.  There was a decrease in induction time as the concentration of the clove seed extract increased. Fingerlings treated with 150mg/l of the extract produced shortest induction time (2.28±0.15 minutes), followed by fish treated with 100 and 125mg/l (3.31±0.55 and 3.07±0.07 minutes, respectively). Longest induction time (10.60±0.98, 7.52±0.25 and 5.96±1.17 minutes) was observed in fingerling sedated with 50, 25 and 75mg/l, respectively. Recovery was significantly faster (2 – 3.92 minutes) in fish treated with lower dosages (25 to 125mg/l) of the clove seed extract. Mortality after 24 hours of recovery were higher (4.79±0.25 and 3.10±0.54 %) in fish anaesthetized with higher (150 and 125mg/l) concentration of clove seed extract, respectively.  The clove seed extract is an effective anesthesia in Clarias fingerling, therefore, could be utilized for transportation of fingerling to reduce stress and mortality.